Análisis de impactos del proyecto de vinculación de la carrera de agronomía en cinco sectores priorizados en base a indicadores sociales, económicos y ambientales en la provincia de Cotopaxi 2020- 2022 - Conterón Villamarín, Dayana Nicole (2022)
This research was conducted in five prioritized sectors of Cotopaxi Province on the Agronomy Career: Cusubamba, Canchagua, Mulalo, Pastocalle, and Guaytacama, to analyze the data obtained from the period 2020 and 2022. This research is exploratory because it was led directly on site; it was shown based on survey techniques and analyzed in the Microsoft Excel computer platform, giving like results in statistical tables. This research used the sustainability methodology of Santiago Sarandon, examining the environmental, economic, and social components. As a result of the 42 questions, 38 indicators are negative, which is 90. 2% and 4 are positive 9.8% with these are: B4. Cost of land that decreased by -0.02%, A5. The level of air pollution decreased by -0.20%, C3. Dependence on external inputs decreased by -0.05%, A1. Access to health and health coverage decreased by -0.44%, so it was possible to analyze the sustainability indicators.